Upaya Pencegahan Korupsi Melalui Pendidikan Anti Korupsi Sejak Dini Di Lembaga Pendidikan - Saputri, Wahyuni; Hasan, Zainudin (Innovative: Journal Of Social Science Research, 2024)
This study examines how anti-corruption character education can be correlated to school and college curricula as a preventive effort in eradicating corrupt practices in Indonesia. Qualitative methods were used in this research and the findings were taken from various sources, such as journals and articles, books, and others. The aim of this research is to improve and strengthen the principles of anti-corruption education in educational institutions and among the younger generation. Currently, corruption in Indonesia continues. Corruption can be caused by personal human factors; family and community; economics and politics; and organization. Prevention of corruption can be done through education. Instilling the values ​​of honesty and responsibility in every individual, especially students as future leaders of the nation, is the main key to eradicating corruption.